Entrepreneurialism and health-promoting retail food environments in Canadian city-regions. (2nd September 2017) - Mah, Catherine L; Hasdell, Rebecca; Minaker, Leia M; Soo, Stephanie D; Cook, Brian; Demaio, Alessandro R
Summary: The retail sector is a dynamic and challenging component of contemporary food systems with an important influence on population health and nutrition. Global consensus is clear that policy and environmental changes in retail food environments are essential to promote healthier diets and reduce the burden of obesity and non-communicable diseases. In this article, we explore entrepreneurialism as a form of social change-making within retail food environments, focusing on small food businesses. Small businesses face structural barriers within food systems. However, conceptual work in multiple disciplines and evidence from promising health interventions tested in small stores suggest that these retail places may have a dual role in health promotion: settings to strengthen regional economies and social networks, and consumer environments to support healthier diets. We will discuss empirical examples of health-promoting entrepreneurialism based on two sets of in-depth interviews we conducted with public health intervention actors in Toronto, Canada, and food entrepreneurs and city-region policy actors in St. John's, Canada. We will explore the practices of entrepreneurialism in the retail food environment and examine the implications for population health interventions. We contend that entrepreneurialism is important to understand on its own and also as a dimension of population health intervention context. A growing social scientific literature offers a multifaceted lens through which we might consider entrepreneurialism not only as a set of personal characteristics but also as a practice in networked and intersectoral cooperation for public and population health.